The Issue of Representativeness in the Lights of the Amended Trade Unions Act - Sierocka, Iwona (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The subject of the deliberations are issues regarding the representativeness and size of workplace trade union organisations after the changes introduced in the Trade Unions Act in 2018. According to the obligatory provisions, the “representativeness” of a trade union organisation is traditionally conditional on its size, but not only the employees, but also other categories of the employed are taken into account. It is, inter alia, about persons providing work under a contract of mandate or a specific work contract and sole proprietors. By expanding the full rights of coalition onto persons performing work on the basis other than employment relationship, the legislator increased the percentage limits decisive in the matter of representativeness. At present, the representative trade union organisation above the workplace level is also an organisation uniting at least 15% of all people performing gainful work under the articles of association, not fewer, however, than 10,000 persons performing gainful work. It works similarly at the workplace level. With reference to workplace trade union organisations which belong to organisations above the workplace level which meet the criteria for representativeness as specified in the Social Dialogue Council Act, at least 8% of the staff of the given employer is required. In the case of workplace trade union organisations which do not participate in such structures, the representativeness is conditional on uniting of at least 15% of persons performing gainful work for the given employer (7% and 10%, respectively, were required earlier). Determining the number of the staff, the employees and persons providing gainful work under other bases being employed for at least 6 months before the commencement of negotiations or arrangements must be included. A significant novelty is the necessity to select a joint representation of the representative organisations at the workplace level that belong to the same Trade Union Federation or National Trade Union Confederation in matters regarding collective rights and interests of the persons performing gainful work.